Perceived Occupational Performance in Youth with Eating Disorders: Treatment-Related Changes. (December 2020) - Coelho, Jennifer S.; Fernandes, Avarna; Suen, Janet; Keidar, Adi; Cairns, Jadine
Background: This study examined changes in performance and satisfaction with self-identified occupational performance goals during a specialized day treatment admission in children and adolescents with eating disorders. Weight-related outcomes for underweight youth were also examined. Methods: A total of 63 youth participated in the study, with admission and discharge data on ratings of self-identified occupational performance goals (measured with the Canadian Occupational Performance Measure) available for 42 participants. Findings: Significant improvements were found in ratings of satisfaction and performance with self-identified goals over the course of treatment. The program was also effective in supporting weight restoration for underweight youth, with a large effect size observed. Implications: A symptom-focused day treatment program for paediatric eating disorders led to improvements in perceived occupational performance. Collaborating with youth to develop self-identified goals in the context of eating disorders treatment can foster autonomy and potentially improve treatment engagement.